1987
DOI: 10.1002/hep.1840070217
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metabolism during acute ethanol administration: A phosphorus-31 nuclear magnetic resonance study on the perfused rat liver under normoxic or hypoxic conditions

Abstract: The effect of ethanol metabolism on the energetic parameters and intracellular pH of the isolated perfused rat liver from fed rats was studied by phosphorus-31 nuclear magnetic resonance spectroscopy. This technique allowed us to analyze nondestructively and in real time the role of low oxygen tension on the possible injurious effect of ethanol on the liver cells. A quantitative analysis of nuclear magnetic resonance data recorded on a perfused rat liver within a 30 mm diameter probe has been performed at 80.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…Interestingly, no significant changes were observed in hepatic intracellular pH, which is determined by the chemical shift difference between the Pi and a-ATP peaks in the 31 P NMR spectra, in any group, indicating that the Cs extract had no severe hepatotoxicity and maintained normoxic conditions. In general, intracellular acidosis can be induced by hepatotoxic reagents and hypoxic conditions (Desmoulin et al 1987;Takahashi et al 1990). Moreover, histopathological findings have revealed that Cs extract does not induce severe hepatotoxic changes in the liver, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no significant changes were observed in hepatic intracellular pH, which is determined by the chemical shift difference between the Pi and a-ATP peaks in the 31 P NMR spectra, in any group, indicating that the Cs extract had no severe hepatotoxicity and maintained normoxic conditions. In general, intracellular acidosis can be induced by hepatotoxic reagents and hypoxic conditions (Desmoulin et al 1987;Takahashi et al 1990). Moreover, histopathological findings have revealed that Cs extract does not induce severe hepatotoxic changes in the liver, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in ATP consumption attributed to depressed Na pump function can theoretically produce a high energy state in the liver (Takahashi et al 1990). When Na pump function is depressed by toxic agents and hypoxic conditions, severe intracellular acidosis is induced (Desmoulin et al 1987;Takahashi et al 1990). However, no such decrease in ATP consumption occurred in the liver of Cs-extract-treated mice, because no severe changes were observed in liver intracellular pH.…”
Section: Discussionmentioning
confidence: 99%
“…The novel phosphorylated pyrrolidine diethyl(2-methylpyrrolidin-2-yl)phosphonate (DEPMPH) was evaluated as a 31 P NMR probe of the pH changes associated with ischemia/reperfusion of rat isolated hearts and livers. In vitro titration curves indicated that DEPMPH exhibited a 4-fold larger amplitude of chemical shift variation than inorganic phosphate yielding an enhanced NMR sensitivity in the pH range of 5.0 -7.5 that allowed us to assess pH variations of less than 0.1 pH units.…”
mentioning
confidence: 99%
“…Because of the dependence of the chemical shift of phosphates on pH (1-3), 31 P NMR spectroscopy has progressively become the standard method for the measurement of intracellular pH (pH i ) 1 in biological systems, mostly using inorganic orthophosphate (P i ) as a naturally occurring pH probe (4 -6). Although this technique was first applied to measure pH in a variety of biological fluids, the development of pulsed Fourier transform NMR and wide-bore supraconducting magnets has soon allowed the noninvasive study of cell cultures and isolated perfused organs under physiologic or pathologic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation